The upside [videorecording (DVD)] - Burger, Neil; Hart, Kevin, 1979-; Cranston, Bryan, 1956-; Kidman, Nicole, 1967- (Universal Pictures Home Entertainment, 2019)
When a recently paroled ex-convict is hired to care for a quadriplegic man, they become friends and give each other a new perspective on life.